Validation of Asarum rosei B.T.Sinn - Sinn, Brandon T. (Phytotaxa, 2017)
It has come to my attention that the designation of the holotype in the protologue of Asarum rosei B.T.Sinn (Sinn, 2017) has been perceived by some to be ambiguous, and thus in conflict with Article 40.2 of the Code (McNeill et al. 2012). Here I validate the name by providing an unambiguous designation for the type.